2020
DOI: 10.1097/yco.0000000000000598
|View full text |Cite
|
Sign up to set email alerts
|

Dopamine D2 up-regulation in psychosis patients after antipsychotic drug treatment

Abstract: Purpose of review Recently, it has been questioned whether the re-emergence of psychotic symptoms following antipsychotic discontinuation or dose reduction is attributable to underlying psychotic vulnerability or to rebound effects of chronic use of antipsychotic medication. It was repeatedly shown that relapse rates are high after discontinuation of maintenance treatment. A potential contributing factor could be the increase in density of postsynaptic dopamine D2 receptors in the striatum and the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 34 publications
0
5
0
Order By: Relevance
“…With the advent of molecular biomedicine and precision medicine the Bradford Hill criterion of 'specificity', or the specific molecular mechanisms that have been found to underlie a strong statistical association, has assumed a dominant position in assessing causality. In the case of our study the association between long-term antipsychotic use and negative outcome is most likely based on the molecular mechanisms of aiDSP (Goff, Tsai, Beal, & Coyle, 1995;Howes et al, 2012;Samaha, Seeman, Stewart, Rajabi, & Kapur, 2007;Thompson, de Vries, & Sommer, 2020) and antipsychotic-induced brain shrinkage largely in fronto-temporal cortical areas due to oxidative stress and neuronal loss (Aderhold, Weinmann, Hägele, & Heinz, 2015;Dorph-Petersen et al, 2005;Fusar-Poli et al, 2013;Raudenska et al, 2013;Vita, De Peri, Deste, Barlati, & Sacchetti, 2015). It is ironic that the recent American Psychiatric Association recommendations for long-term antipsychotic use in patients with schizophrenia recommend switching to clozapine when patients stop improving on their initial antipsychotic medication, in that clozapine has been found to mitigate the molecular sensitivity reaction in the dopamine system aiDSP caused by the long-term use of antipsychotic medications, and also to reduce the long term mortality risk associated with all other antipsychotic medications.…”
mentioning
confidence: 75%
“…With the advent of molecular biomedicine and precision medicine the Bradford Hill criterion of 'specificity', or the specific molecular mechanisms that have been found to underlie a strong statistical association, has assumed a dominant position in assessing causality. In the case of our study the association between long-term antipsychotic use and negative outcome is most likely based on the molecular mechanisms of aiDSP (Goff, Tsai, Beal, & Coyle, 1995;Howes et al, 2012;Samaha, Seeman, Stewart, Rajabi, & Kapur, 2007;Thompson, de Vries, & Sommer, 2020) and antipsychotic-induced brain shrinkage largely in fronto-temporal cortical areas due to oxidative stress and neuronal loss (Aderhold, Weinmann, Hägele, & Heinz, 2015;Dorph-Petersen et al, 2005;Fusar-Poli et al, 2013;Raudenska et al, 2013;Vita, De Peri, Deste, Barlati, & Sacchetti, 2015). It is ironic that the recent American Psychiatric Association recommendations for long-term antipsychotic use in patients with schizophrenia recommend switching to clozapine when patients stop improving on their initial antipsychotic medication, in that clozapine has been found to mitigate the molecular sensitivity reaction in the dopamine system aiDSP caused by the long-term use of antipsychotic medications, and also to reduce the long term mortality risk associated with all other antipsychotic medications.…”
mentioning
confidence: 75%
“…The review articles which did not consider DSP important in the etiology of TRS did not make any comments about worsening psychosis due to aripiprazole. However, this phenomenon is often observed in clinical practice [ 33 , 34 , 36 ]. Unfortunately, only one study examined the possibility that DS may be involved in the worsening of psychosis by the addition of or switching to aripiprazole [ 84 ]; that retrospective study of 264 patients whose antipsychotic medication was switched to aripiprazole revealed that 56 of 70 patients who were judged as having DS consequently showed a failure of the switch to aripiprazole, and 16 of the 56 patients exhibited a worsening of positive symptoms.…”
Section: The Effect Of Aripiprazole On Dspmentioning
confidence: 99%
“…However, there are recent reviews on TRS discussing that DSP is not likely to be important as the etiology of the disease [ 33 , 34 ]. Even articles discussing the merit-demerit balance of the long-term use of antipsychotics note that DSP has been one of the leading problems with a potential negative impact on the clinical course of patients with schizophrenia, but the articles’ authors raised some cautions regarding DSP [ 35 , 36 ]. These four review articles dealt with the DSP theory, but they concluded that the DSP theory was not based on reliable evidence.…”
Section: Introductionmentioning
confidence: 99%
“…In patients with schizophrenia, the findings vary broadly according to different types of studies (eg, neuropathological, nuclear isotope imaging), sometimes with contradictory results, 7 and are also confounded by neuroadaptations caused by medications. 42 Our study has limitations; we did not examine the levels of neurotransmitters in different brain regions, or whether the density of receptors was affected to a different extent in those regions. In addition, the timing of symptom presentation (eg, psychotic-like behavior and memory changes) was examined at 4 time points, 2 of them corresponding to the most symptomatic stage (days 10-11 and 18-19), but without detailed tracking of which symptom and receptor (D1R or D2R) were affected first.…”
Section: Discussionmentioning
confidence: 98%